Increasing the resting time between drop jumps lessens delayed-onset muscle soreness and limits the extent of prolonged low-frequency force depression in human knee extensor muscles - Kamandulis, S.; Mickevicius, M.; Snieckus, A.; Streckis, V.; Montiel-Rojas, D.; Chaillou, T.; Westerblad, H.; Venckunuas, T. (European Journal of Applied Physiology, 2021)
Purpose Unaccustomed eccentric contractions generally result in a long-lasting contractile impairment, referred to as prolonged low-frequency force depression (PLFFD), and delayed-onset muscle soreness (DOMS). We here used repeated drop jumps (DJs) as an eccentric contraction model and studied the effects of increasing the time between DJs from 20 s to 5 min. We hypothesized that both PLFFD and DOMS would be less marked at the longer DJ interval due to the longer time to restore structural elements between DJs.